Evolution of logic as an information processing mechanism in advanced biological systems. (November 2022) - Burgin, Mark
Abstract: Logic plays an important role in biological evolution. Some researchers even assume that evolution can be seen as a process of discovering the logic that works well in a particular environment. At the same time, logic can be treated as a biological system, or a superorganism, evolution of which goes in the social environment with its societal space and time. In this paper, syntactic aspects of the evolution of logic are studied demonstrating how logic evolves from the simplest logical species to the higher and higher logical species.